Development of Android-Based Interactive Media for History Subjects at SMA Negeri 1 Krueng Barona Jaya - Alfrian*, Muhamad; Sakdiyah, Sakdiyah; Kamza, Muhjam (Universitas Syiah Kuala, 2024)
This research is entitled Development of Android-Based Interactive Media for History Subjects at SMA Negeri 1 Krueng Barona Jaya. This research was conducted because there are still many teachers who have not maximized the use of gadgets as learning media in the modern era. This aim of this research is to determine the development of android-based interactive media in history subjects at SMA Negeri 1 Krueng Barona Jaya and to determine the feasibility of android-based interactive media in history subjects at SMA Negeri 1 Krueng Barona Jaya. This research is a type of research and development (RD). This research was developed with five steps of ADDIE model, namely 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. Data collection techniques use interview, documentation, expert validation sheet. The data analysis technique uses descriptive statistical techniques with percentage formulas. This research produces learning media in the form of android-based interactive media in the form of an application namely History Application (HistoApp)with learning material The arrival European nations to Indonesia which contains audio, teks, and images. Based on validation carried out with material experts, a percentage of 88% was obtained in the very feasible category. Based on validation carried out with media experts, a percentage of 80% was obtained in the feasible category. The expert validation results show that the HistoApp application media product is worthy of being tested in the learning process in class of XI-IIS-1 SMA Negeri 1 Krueng Barona Jaya. The result of the implementation trial before developing android-based interactive media obtained an average students score of 70 and the average students score after developing android-based interactive media was 80. So it can be concluded that the android-based interactive media product for history subjects at SMA Negeri 1 Krueng Barona Jaya with the learning material The arrival of European nations to Indonesia which has been developed by researcher is feasible for use in the history learning process.